Sleep deprivation and its association with depression in first-year medical and dental students in Kanchipuram District, Tamil Nadu, India - Prasan Norman; E. Karthikeyan; D. Thirunaaukarasu; S. Hafeez (Orapuh Journal, 2023)
Introduction Sleep deprivation is a major problem for college students. A single sleepless night can make one irritable and moody the following day, it is not surprising that chronic sleep deprivation may lead to long-term mood disorders like depression. Medical and dental students are exposed to tremendous levels of pressure due to academic demands which could ultimately potentiate sleep deprivation. Purpose The objective of this study is to grade the level of sleep deprivation in first-year medical and dental students, to grade the level of depression in first-year medical and dental students, and to assess the relationship between sleep deprivation and depression. Methods 168 students participated in this study. They were briefed about the study. Two questionnaires were used for the study. The questionnaires used were the Epworth Sleepiness Scale (to assess sleep deprivation) and Beck’s Depression Inventory (to assess depression). Statistical Package for Social Sciences (SPSS) software was used for statistical analysis. Results 72% of the participants suffered from moderate sleep deprivation and 26% suffered from borderline clinical depression. As sleep deprivation increased in the participants, their depression also increased. There was a statistically significant positive correlation between the depression score and the sleeping score (p<0.05). However, there was no association between gender and depression (p>0.05). Conclusion Policy efforts should be directed toward primary and secondary prevention programs that enforce sleep education interventions, particularly among first-year college students. interventions need to be youth-friendly, acceptable, feasible, and non-stigmatizing.